Manfaat Komunikasi Guru dalam Memberikan Motivasi Belajar Kepada Siswa di MTs - Nasri, Nasri (Lembaga Yasin AlSys, 2022)
Communication is the process of delivering or receiving messages from one person to another, either directly or indirectly, in writing, verbally or in nonverbal language. Teachers' communication skills in learning activities include 4 main abilities, namely: First, the ability of teachers to develop positive attitudes in learning activities. This ability consists of: (1) Recognizing the strengths and weaknesses of students in learning activities. (2) Helping students to develop self-confidence in learning activities. (3) Help clarify thoughts and feelings so that others can understand and exchange ideas in learning activities. Learning motivation comes from the Latin word